Constipation is a Major Complication after Posterior Sagittal Anorectoplasty for Anorectal Malformations in Children - Ching-Fang Huang; Hung-Chang Lee; Chun-Yan Yeung; Wai-Tao Chan; Chuen-Bin Jiang; Jin-Cherng Sheu; Nien-Lu Wang; Jr-Rung Lin (Elsevier, 2012)
To assess whether constipation or fecal incontinence is a major late complication after posterior sagittal anorectoplasty in patients with anorectal malformation (ARM). Methods: We retrospectively enrolled 188 children, 85 low-type ARM (L-ARM) and 103 high-type ARM (H-ARM), who had complete medical records of bowel habits and medication histories after posterior sagittal anorectoplasty for anorectal malformation in Mackay Memorial Hospital. Stool characteristics as well as physical and medication history were evaluated. The symptom severity (SS) scoring system was used to assess changes in bowel habits. Results: During a mean follow-up period of 4.3 years, constipation was found to be the most common late complication in both groups of patients (64.5% in the L-ARM group and 78.6% in the H-ARM group). Compared to constipation, stool incontinence was much less frequent, with 4.7% in L-ARM and 3.9% in H-ARM. There was no significant difference in mean SS scores between the two groups. Conclusion: Constipation was the most common late sequela in children after correction of ARM in our study.